Combined Preimplantation Genetic Testing for Genetic Kidney Disease: Genetic Risk Identification, Assisted Reproductive Cycle, and Pregnancy Outcome Analysis - Xiao, Min; Shi, Hua; Rao, Jia; Xi, Yanping; Zhang, Shuo; Wu, Junping; Zhu, Saijuan; Zhou, Jing; Xu, Hong; Lei, Caixia; Sun, Xiaoxi (Frontiers in Medicine, 2022)
Background Genetic kidney disease is a major cause of morbidity and mortality in neonates and end-stage renal disease (ESRD) in children and adolescents. Genetic diagnosis provides key information for early identification of congenital kidney disease and reproductive risk counseling. Preimplantation genetic testing for monogenic disease (PGT-M) as a reproductive technology helps prospective parents to prevent passing on disease-causing mutations to their offspring. Materials and Methods A retrospective cohort of couples counseled on PGT who had a risk to given birth to a child with genetic kidney disease or had a history of prenatal fetal kidney and urinary system development abnormalities from 2011 to 2021. Through a combination of simultaneously screening for aneuploidy and monogenic kidney disease, we achieved reproductive genetic intervention. Results A total of 64 couples counseled on PGT for monogenic kidney disease in a single reproductive center during the past 10 years, of whom 38 different genetic kidney diseases were identified. The most frequent indications for referral were autosomal recessive disease (54.7%), then autosomal dominant disease (29.7%), and X-linked disease (15.6%). Polycystic kidney disease was the most common diseases counted for 34.4%. After oocyte-retrieval in all of 64 females, a total of 339 embryos were diagnosed and 63 embryos were transferred in succession. Among 61 cycles of frozen-embryo transfer (FET), ongoing pregnancy/live birth rate (OP/LBR) reached 57.38%. The cumulative OP/LBR in our cohort for the 64 couples was 54.69%. In addition, we have carried out expanded carrier screening (ECS) in all the in vitro fertilization (IVF) couples performed PGT covering 7,311 individuals. The carrier frequency of the candidate genes for monogenic kidney diseases accounted for 12.19%. Conclusion Overall, the customization PGT-M plan in our IVF center is pivotal to decreasing the morbidity and implementing reproductive genetic intervention of genetic kidney disease.